1995
DOI: 10.1093/tropej/41.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Differential Clinical and Epidemiological Features in Children with Campylobacter Diarrhoea, Mixed-agent Diarrhoea and Campylobacter Diarrhoea plus Parenteral Infections

Abstract: A prospective study of 111 young Peruvian children with Campylobacter jejuni diarrhoea showed that it behaves as an endemic enterotoxigenic-like, waterborne, milkborne, and zoonotic disease. Although there were no definite differential features between pure C. jejuni diarrhoea, mixed-agent diarrhoea, and C. jejuni diarrhoea plus parenteral infections, children with C. jejuni diarrhoea plus parenteral infections were all inpatients, were more frequently malnourished and more frequently exhibited systemic sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In this study, we did not have possibilities to look for Campylobacter spp. However, this pathogen has been found to be associated with diarrhea in children in many studies [5,73,158,227]. In Vietnam, a study in children less than 5 years of age carried out by Isenbarger et al [111] showed that Campylobacter was found in 6.8% of cases.…”
Section: Etiology and Epidemiology Of Diarrhea In Children Less Than mentioning
confidence: 99%
“…In this study, we did not have possibilities to look for Campylobacter spp. However, this pathogen has been found to be associated with diarrhea in children in many studies [5,73,158,227]. In Vietnam, a study in children less than 5 years of age carried out by Isenbarger et al [111] showed that Campylobacter was found in 6.8% of cases.…”
Section: Etiology and Epidemiology Of Diarrhea In Children Less Than mentioning
confidence: 99%